Lateral Transorbital Neuroendoscopic Approach to the Lateral Cavernous Sinus - Bly, Randall A.; Ramakrishna, Rohan; Ferreira, Manuel; Moe, Kris S. (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective To design and assess the quality of a novel lateral retrocanthal endoscopic approach to the lateral cavernous sinus.Design Computer modeling software was used to optimize the geometry of the surgical pathway, which was confirmed on cadaver specimens. We calculated trajectories and surgically accessible areas to the middle fossa while applying a constraint on the amount of soft tissue retraction.Setting Virtual computer model to simulate the surgical approach and cadaver laboratory.Participants The authors.Main Outcome Measures Adequate surgical access to the lateral cavernous sinus and adjacent regions as determined by operations on the cadaver specimens. Additionally, geometric limitations were imposed as determined by the model so that retraction on soft tissue structures was maintained at a clinically safe distance.Results Our calculations revealed adequate access to the lateral cavernous sinus, Meckel cave, orbital apex, and middle fossa floor. Cadaveric testing revealed sufficient access to these areas using <10 mm of orbital retraction.Conclusions Our study validates not only the use of computer simulation to plan operative approaches but the feasibility of the lateral retrocanthal approach to the lateral cavernous sinus.
Keywords: cavernous sinus; endoscopic; pituitary; transnasal; transsphenoidal; transorbital